First Insights on Resistance and Virulence Potential of Escherichia coli from Captive Birds of Prey in Portugal - Rita Magalhães; Raquel Abreu; Gonçalo Pereira; Eva Cunha; Elisabete Silva; Luís Tavares; Lélia Chambel; Manuela Oliveira (MDPI AG, 2024)
Captive birds of prey are often used for pest control in urban areas, while also participating in falconry exhibitions. Traveling across the country, these birds may represent a public health concern as they can host pathogenic and zoonotic agents and share the same environment as humans and synanthropic species. In this work, Escherichia coli from the cloacal samples of 27 captive birds of prey were characterized to determine their pathogenic potential. Isolates were clustered through ERIC-PCR fingerprinting, and the phylogenetic groups were assessed using a quadruplex PCR method. Their virulence and resistance profile against nine antibiotics were determined, as well as the isolates' ability to produce extended-spectrum β-lactamases (ESBLs). The 84 original isolates were grouped into 33 clonal types, and it was observed that more than half of the studied isolates belonged to groups D and B2. Most isolates presented gelatinase activity (88%), almost half were able to produce biofilm (45%), and some were able to produce α-hemolysin (18%). The isolates presented high resistance rates towards piperacillin (42%), tetracycline (33%), and doxycycline (30%), and 6% of the isolates were able to produce ESBLs. The results confirm the importance of these birds as reservoirs of virulence and resistance determinants that can be disseminated between wildlife and humans, stressing the need for more studies focusing on these animals.